Murabahah sale in practice: procedure and issues in consumer and trade financing - Sadique, Muhammad Abdurrahman (Global Academic Excellence (GAE), 2017)
In Murabahah financing practised by Islamic financial institutions, instead of extending a loan facility to the client for purchasing commodities required by him, the Islamic bank purchases the commodity from the supplier first and thereafter sells it to the client usually on deferred payment basis, at an agreed fixed price comprising the cost incurred by the bank and an additional margin of profit. In the context of financing, Murabahah takes the form of a complex procedure comprising several transactions, reflecting several relationships between the parties involved. Being a mode of sale, all rules and conditions that are relevant to sale transactions remain applicable in Murabahah even when it is used for financing purposes. Murabahah is commonly used to finance the purchase of assets in a variety of forms, including financing consumer items as well as in trade financing, both through local purchase as well as import. A study of the procedural aspects of Murabahah would reveal that its proper implementation in a financing context is challenging. In order to overcome issues arising in Murabahah based financing, implementation of equity based modes such as Musharakah should be attempted where possible, such as in the context of trade financing. The current paper analyses important aspects involved in the application of Murabahah in the above areas, scrutinising practical aspects that are required to be carefully observed for the validity of the procedure in shari‘ah.